Visceral Leishmaniasis-HIV Coinfection as a Predictor of Increased Leishmania Transmission at the Village Level in Bihar, India - Cloots, Kristien (Front Cell Infect Microbiol, 2021)
BACKGROUND: Visceral leishmaniasis (VL) is on the verge of being eliminated as a public health problem in the Indian subcontinent. Although Post-kala-azar dermal leishmaniasis (PKDL) is recognized as an important reservoir of transmission, we hypothesized that VL patients co-infected with Human Immunodeficiency Virus (HIV) may also be important reservoirs of sustained leishmania transmission. We therefore investigated to what extent cases of PKDL or VL-HIV are associated with VL incidence at the village level in Bihar, India. METHODS: VL, VL-HIV, and PKDL case data from six districts within the highly VL-endemic state of Bihar, India were collected through the Kala-Azar Management Information System for the years 2014–2019. Multivariate analysis was done using negative binomial regression controlling for year as a fixed effect and block (subdistrict) as a random effect. FINDINGS: Presence of VL-HIV+ and PKDL cases were both associated with a more than twofold increase in VL incidence at village level, with Incidence Rate Ratios (IRR) of 2.16 (95% CI 1.81–2.58) and 2.37 (95% CI 2.01–2.81) for VL-HIV+ and PKDL cases respectively. A sensitivity analysis showed the strength of the association to be similar in each of the six included subdistricts. CONCLUSIONS: These findings indicate the importance of VL-HIV+ patients as infectious reservoirs for Leishmania, and suggest that they represent a threat equivalent to PKDL patients towards the VL elimination initiative on the Indian subcontinent, therefore warranting a similar focus.